Cyber Grooming sebagai Ancaman Seksual di Era Digital: Perlindungan Anak Korban Cyber Grooming (Studi Kasus Yayasan Kakak Surakarta) - Divana Frida Lausiana; Fery Dona (AHKAM, 2025)
The development of digital technology has opened new spaces of interaction for children and adolescents, while simultaneously increasing their vulnerability to online sexual crimes such as cyber grooming, which is carried out gradually through emotional manipulation on digital platforms. Nationally, cases of sexual violence against children, including those occurring in digital forms, show an increasing trend, while in Surakarta the Yayasan KAKAK has recorded a rise in reports of cyber grooming among children aged 8–12 years. This study aimed to analyze the forms of protection provided by Yayasan KAKAK to victims and to examine the criminal act of cyber grooming from the perspective of Indonesian positive law and Islamic criminal law. The research employed a qualitative approach through interviews, a review of legal assistance practices conducted by Yayasan KAKAK, and an analysis of regulations related to child protection and sexual violence. The findings show that cyber grooming generally begins with seemingly normal communication that subsequently develops into psychological manipulation, resulting in anxiety and trauma for victims; Yayasan KAKAK responds through comprehensive assistance that includes emotional assessment, counseling, and preventive education via outreach roadshows. From the perspective of Indonesian positive law, cyber grooming can be prosecuted under child protection and sexual violence legislation, although law enforcement is often constrained by limitations in digital evidence. In Islamic criminal law, cyber grooming is positioned as a form of abuse involving non-physical ikrah (coercion), whereby victims are exempt from liability and perpetrators are subject to uqubah ta‘zīr (discretionary punishment) based on relevant Qur’anic verses and hadith. This study underscores the importance of synergy between regulatory strengthening, capacity building of support institutions, and systematic preventive approaches to protect children from the threat of digital sexual violence.